(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sensor Nodes play a vital role in wireless sensor networks (WSN). Routing protocols helps to enhance the lifespan and energy efficiency of battery powered sensor nodes. In wireless sensor network similar nodes are grouped to form clusters. Moth flame optimization algorithm is used for selecting the cluster head. MFO algorithm helps to solve the complex real-world problems. In this paper, we propose Moth flame optimization algorithm for Wireless sensor network. This paper presents the steps to form the clustering network in WSN and the transmission strategy.